Introduction: Migration to the Center Project opens Europe Beyond Borders - Pěničková, Daniela (Lidé města, 2014)
The presented papers are a collection of conference contributions. The conference titled Beyond Borders: Migration and (In)Equality in Central Europe in Comparison was both the major and closing event of an 18-month international project Migration to the Center funded by the EU program Europe for Citizens, the International Visegrad Fund, and the Ministry of Foreign Affairs of the Czech Republic. The project examined how the EU Community acquis and other instruments impact migration and integration policies, practices, and lives of migrants in Central Europe and beyond. The participatory countries were represented by the following institutions: The Center for Independent Journalism (Hungary), the Institute of Public Affairs (Poland), the Peace Institute (Slovenia), the Human Rights League (Slovakia), and People in Need and the Multicultural Center (Czech Republic), the latter serving as the project coordinator. The project aimed to create an active network of Central European partners and their counterparts from the rest of Europe focused on migration and integration while drawing the attention of policy makers, experts, and the public to the common and country-specific challenges and successes in the implementation of migration legislation across the region. Its objective was to contribute to the cultivation of the migration-related issues debate and create conditions for inclusion of migrants into the policy-making process. The project covered the following themes considered crucial by the participating countries in the migration and integration process: (a) work and residence permit, (b) family reunification, and (c) study and training in the EU. The themes were explored by each of the project partners via two expert analysis articles, five migrant outputs related to the theme (in a variety of forms ranging from a recorded interview to photo stories, poetry, and short articles), and a national public debate in each country that was recorded and provided with English subtitles. These outcomes have been publicized on the project’s web pages www.migrationtothecentre.migraceonline.cz.